2000
DOI: 10.1348/014466600164372
|View full text |Cite
|
Sign up to set email alerts
|

Social categorizations, social comparisons and stigma: Presentations of self in people with learning difficulties

Abstract: Self-categorization theory stresses the importance of the context in which the meta-contrast principle is proposed to operate. This study is concerned with how 'the pool of psychologically relevant stimuli' (Turner, Hogg, Oakes, Reicher & Wetherell, 1987, p. 47) comprising the context is determined. Data from interviews with 33 people with learning difficulties were used to show how a positive sense of self might be constructed by members of a stigmatized social category through the social worlds that they des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
84
1
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(95 citation statements)
references
References 21 publications
9
84
1
1
Order By: Relevance
“…It has been found that self-comparison plays an important role in the self-esteem of people with learning disabilities (Crabtree and Rutland, 2001), with strategies including making downward comparisons to compare the self favourably with people who are less able, and making lateral comparisons emphasising similarity to people without learning disabilities helping to maintain self-esteem (Dagnan & Sandhu, 1999;Finlay & Lyons, 2000). As older people in the general population seem to engage in self-enhancing social comparisons (Rickabaugh & Tomlinson-Keasey, 1997;Sherrard, 1998), it seems reasonable to assume that the findings of studies such as Finlay and Lyons (2000) could be applicable to older people with learning disabilities although the studies have not focused on older people specifically. Finlay and Lyons (2000) make the point that someone who may seem to observers to have a stigmatised identity may not actually experience their identity in this way.…”
Section: Identity and People With Learning Disabilitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been found that self-comparison plays an important role in the self-esteem of people with learning disabilities (Crabtree and Rutland, 2001), with strategies including making downward comparisons to compare the self favourably with people who are less able, and making lateral comparisons emphasising similarity to people without learning disabilities helping to maintain self-esteem (Dagnan & Sandhu, 1999;Finlay & Lyons, 2000). As older people in the general population seem to engage in self-enhancing social comparisons (Rickabaugh & Tomlinson-Keasey, 1997;Sherrard, 1998), it seems reasonable to assume that the findings of studies such as Finlay and Lyons (2000) could be applicable to older people with learning disabilities although the studies have not focused on older people specifically. Finlay and Lyons (2000) make the point that someone who may seem to observers to have a stigmatised identity may not actually experience their identity in this way.…”
Section: Identity and People With Learning Disabilitiesmentioning
confidence: 99%
“…As older people in the general population seem to engage in self-enhancing social comparisons (Rickabaugh & Tomlinson-Keasey, 1997;Sherrard, 1998), it seems reasonable to assume that the findings of studies such as Finlay and Lyons (2000) could be applicable to older people with learning disabilities although the studies have not focused on older people specifically. Finlay and Lyons (2000) make the point that someone who may seem to observers to have a stigmatised identity may not actually experience their identity in this way. The stigmatised identity depends on a certain set of comparisons being made, and the individual may view different comparison dimensions as salient, and make a different set of comparisons that are more useful to them and represent them in a more positive way.…”
Section: Identity and People With Learning Disabilitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, she claimed that other people were more intellectually disabled than she was, and that this applied to people who she defined as 'people who are living in group homes and needs a lot of help.' Several authors suggest that some intellectually disabled people tend to describe themselves by comparing their abilities to others who need more support (Dagnan and Sandhu 2001;Finlay and Lyons 2000). It seemed that Frida was using the same kind of comparison in order to be seen as 'almost ordinary.…”
Section: Self-presentations and The Label Intellectual Disabilitymentioning
confidence: 99%
“…Uwzględniając znaczenie porównania społecznego w doświadczaniu skutków stygmatyzacji, podkreślają jego moderującą rolę w relacji między percepcją przejawów stygmatyzujących a samooceną (por. Finlay, Lyons 2000). Dostrzeżona rola czynników pośredniczących w wyjaśnianiu związku między stygmatyzacją a samooceną ujawniła jego niezwykle złożony charakter.…”
unclassified